Correlation between smartphone addiction and dysfunctional attitudes in nursing/midwifery students - Serin, Emine Kaplan; Durmaz, Yadigar Cevik; Polat, Hilal Turkmen (Wiley, 2019)
Purpose The aim of this study is to determine the correlation between smartphone addiction and dysfunctional attitudes. Design and Methods This descriptive study was conducted with the students of Nursing/Midwifery Department of a state university from March 01 to April 01, 2018. Findings Participant students had a mean score of 27.25 +/- 11.41 in smartphone addiction scale and a mean score of 27.96 +/- 14.74 in dysfunctional attitudes scale. The number of students' friends was found to affect their problem solving skills. Loneliness levels of participant students affected their dysfunctional attitude scores. Practice Implications It is highly important for our country to have sufficient knowledge of smartphone addiction, detect the dysfunctional attitudes and develop nursing care methods
Keywords: dysfunctional attitudes; midwife; nurse; smartphone addiction